Improvement on the Catalytic Performance using Dual Lipases System in the Synthesis of Ferulate Esters - Salina Mat Radzi; Nurul Jannah Abd Rahman; Hanina Mohd Noor; Norlelawati Arifin (Trans Tech Publications, Switzerland, 2024)
A novel approach of dual lipases system was successfully carried out in improving the synthesis of ferulate esters between ethyl ferulate and olive oil. Combination of Novozym 435 and Lipozyme RMIM were used as biocatalyst to improve the reaction performance. Different reaction parameters (ratio of lipases, reaction time, lipase dosage, substrate molar ratio and reaction temperature) were analyzed systematically. A high conversion of ferulate esters (85%) was obtained after 12 hrs of reaction time at optimal conditions of 1:9 w/w (Novozym 435/Lipozyme RMIM), 80mg of lipase and 1:4 ethyl ferulate:olive oil at 60 ?C.